PENINGKATAN HASIL BELAJAR SEJARAH POKOK BAHASAN ZAMAN PENDUDUKAN MILITER JEPANG DI INDONESIA MELALUI MODEL PEMBELAJARAN PICTURE AND PICTURE KELAS XI IPS4 DI SMAN 1 BARABAI TAHUN PELAJARAN 2013/2014 - Saupiah Saupiah (JURNAL SOCIUS, 2014)
The purpose of this research is to find out the increase of the activities and learning outcomes of history at eleven 4 of SMAN 1 Barabai in the School Year of 2013/2014. One of the ways to get students interested in and be able to apply it in everyday life, a different model of learning, that is, more interactive, non-monotonous, giving more freedom for the students to think, as well as involving the students in the teaching-learning process more directly is needed. So that the teaching and learning can involve students directly and make students as the center of learning.wich can be improved by using picture and picture as teaching strategy. The approach which used on this classroom action research is qulitative analysis, which emphasizes on the research problem especially in improving the motivation and study result of students in history. Therefore, the problem can be identified and analyzed then found alternative solutions, there 34 students as samples on XI IPS 4 classteaching SMA Negeri 1 Barabai. The results of this study reveal that student learning outcomes are increased. In cycle I,of the 32 students, there are 6 people or 19 % of students who achieve complete mastery level and in cycle II, the mastery level which is attained by all of the students is as expected that is 100%.Key Words : Learning Outcomes , History ,  learning Model Picture and Picture